Characterization of waste of soda-lime glass generated from lapping process to reuse as filler in composite materials as thermal insulation - Galvão,A. C. P. (2015)
AbstractThe beneficiation plate process by soda-lime glass lapping in the glass industry generates, an untapped residue (waste). The waste of this material is sent to landfills, causing impact on the environment. This work aimed to characterize and evaluate the waste of soda-lime glass (GP) lapping. After its acquisition, the GP was processed by grinding and sieving and further characterized by the chemical/mineralogical analysis (XRF, EDS and XRD), SEM morphology, particle size by laser diffraction, thermogravimetric analyses (TGA and DSC) and thermophysical analyses. It was observed that the GP particles are irregular and micrometric with the predominant presence of Na, Si and Ca elements characteristic of amorphous soda-lime glass. The assessment of the chemical/mineralogical, morphological, thermophysical and thermal gravimetric characteristics of GP suggest its reuse as reinforcing fillers or filler in composite materials to obtain thermal insulation.